ART AS A REFLECTION OF SOCIETY: EXAMINING GENDER EQUALITY THROUGH CREATIVE EXPRESSION - Islomova Sevinch Botirjon qizi (Web of Journals Publishing, 2023)
This article delves into the intersection of art and gender equality, examining how creative expression serves as a reflection of societal norms, challenges, and progress in the realm of gender equality. Art has historically been a powerful vehicle for addressing and challenging gender disparities, reflecting the evolving status of women, among others. By exploring diverse forms of artistic expression, this study illustrates how art both mirrors and influences the journey toward gender equality, underscoring its role in shaping societal attitudes and promoting meaningful change.
Keywords: Art, Gender Equality, Creative Expression, Society, Reflection, Gender Disparities.